Investigation of manual handling training practices in organisations and beliefs regarding effectiveness - Hilary McDermott; Cheryl Haslam; Stacy Clemes; Claire Williams; Roger Haslam (2012)
Manual handling activities at work can result in a wide range of musculoskeletal disorders (MSDs). In Europe, the European Union Directive 90/269/EEC e Manual Handling of Loads sets out a hierarchy of measures aimed at reducing the risks of manual handling and training is one of the obligations on employers. This study involved a survey of current practices in relation to manual handling training and sought to identify components believed to be effective. One hundred and fifty telephone interviews were conducted with representatives from UK organisations and training consultancies across a wide range of industry sectors. The majority of participating employer organisations had undertaken some form of manual handling training in the previous 12 months. Responses indicated that induction of new staff and statutory requirements are the main drivers for manual handling training. The majority of organisations surveyed conduct in-house training rather than out sourcing training to consultants. Sickness absence is regarded as the main outcome measure of effectiveness. Survey respondents considered that manual handling training is more effective if it is tailored to specific industry and task demands. Practical elements in training were believed to reinforce learning, particularly if tailored to individual job demands. Understanding how training occurs at present and beliefs surrounding this are a valuable precursor to developing guiding principles for future manual handling training programmes. Relevance to industry: One ergonomic solution for safe manual handling is employee training. This study investigated current practice of manual handling training to reduce the risks of MSDs